Задачи и функции туристического страноведения - Артёменко, С. В.; Artemenko, S. V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Характеризуются основные задачи и функции туристического страноведения. Рассматриваются проблемы содержания учебного туристического страноведения, его соотношения с другими дисциплинами цикла подготовки специалистов в сфере туризма и гостеприимства. Artemenko S. V. Tasks and Functions of Tourism Geography. Characterized by the main tasks and functions of tourism geography. The problems of the content of educational tourism geography, its relationship with other disciplines cycle of training in the field of tourism and hospitality.
Tasks and Functions of Tourism Geography
Keywords: страноведение; туристическое страноведение; задачи и функции туристического страноведения; содержание туристического страноведения; geography; tourism geography; tourism geography tasks; the content of tourist geography